(3GdbGehS GdeMjW hGdbCHhS GdhSjWs - (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3GdMeO ddg efWb GdHdZGA YGddZQa GdHhGOi hHYO aEf ddYde QjGVkG hUjGVkG hEf Yde GddZI gh GdcGad HEHQGR CSQGQ GdLejY hCSejJg (B" (3GdbGehS GdeMjW (B" s
(3BNQgG (B:s
(3hjGA GdLRe GdefHSW (B: (3QCjJ YHOi Gddg , de JSbW dCfg dG Nda YfgG bGd eDdag gPG BNQ GdbGehS GdeMjW hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3CKHJ GdehGO HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B179 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs